Genetic, Epigenetic and Phenotypic Diversity of Four Bacillus velezensis Strains Used for Plant Protection or as Probiotics - Reva, Oleg N.; Swanevelder, Dirk Z. H.; Mwita, Liberata A.; Mwakilili, Aneth David; Muzondiwa, Dillon; Joubert, Monique; Chan, Wai Yin; Lutz, Stefanie; Ahrens, Christian H.; Avdeeva, Lylia V.; Kharkhota, Maksim A.; Tibuhwa, Donatha; et al. (Frontiers in Microbiology, 2019)
Bacillus velezensis strains are applied as ecologically safe biopesticides, plant growth promoting rhizobacteria (PGPR), and in veterinary probiotics. They are abundant in various environments including soil, plants, marine habitats, the intestinal micro-flora, etc. The mechanisms underlying this adaptive plasticity and bioactivity are not well understood, nor is it clear why several strains outperform other same species isolates by their bioactivities. The main objective of this work was to demonstrate versatility of bioactivities and lifestyle strategies of the selected B. velezensis strains suitable to serve as model organisms in future studies. Here, we performed a comparative study of newly sequenced genomes of four B. velezensis isolates with distinct phenotypes and isolation origin, which were assessed by RNA sequencing under the effect of root exudate stimuli and profiled by epigenetic modifications of chromosomal DNA. Among the selected strains, UCMB5044 is an oligotrophic PGPR strain adapted to nutrient poor desert soils. UCMB5113 and At1 are endophytes that colonize plants and require nutrient rich media. In contrast, the probiotic strain, UCMB5007, is a copiotroph, which shows no propensity to colonize plants. PacBio and Illumina sequencing approaches were used to generate complete genome assemblies, tracing epigenetic modifications, and determine gene expression profiles. All sequence data was deposited at NCBI. The strains, UCMB5113 and At1, show 99% sequence identity and similar phenotypes despite being isolated from geographically distant regions. UCMB5007 and UCMB5044 represent another group of organisms with almost identical genomes but dissimilar phenotypes and plant colonization propensity. The two plant associated strains, UCMB5044 and UCMB5113, share 398 genes putatively associated with root colonization, which are activated by exposure to maize root exudates. In contrast, UCMB5007 did not respond to root exudate stimuli. It was hypothesized that alterations in the global methylation pattern and some other epigenetic modifications enable adaptation of strains to different habitats and therefore may be of importance in terms of the biotechnological applicability of these bacteria. Contrary, the ability to grow on root exudates as a sole source of nutrients or a strong antagonism against phytopathogens showed by the strains in vitro cannot be considered as good predictors of PGPR activities.